HOW TO INCLUDE THE STUDENTS WITH SPECIAL NEEDS INTO ORDINARY CLASSROOMS (Conferencea, 2022)
Science achievement among students with special disabilities is typically far lower than that of their classmates. Significant challenges with academic abilities (such as reading, math, and writing), behavioral issues, and a lack of prior comprehension of fundamental ideas are some of the causes of this. Despite this dismal outlook, there is a lot of information on how to greatly enhance scientific success for kids with exceptional needs. According to a recent thorough meta-analysis, inquiry education that incorporates the proper scaffolds and supports can dramatically raise students' scientific success who have special needs. The supports and scaffolding that special needs children need to succeed in inquiry-based education will be outlined in this article.